2012
DOI: 10.1002/cm.21071
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases in animal cell cytokinesis: An occupation by the one percent

Abstract: Rho GTPases are molecular switches that elicit distinct effects on the actomyosin cytoskeleton to accurately promote cytokinesis. Although they represent less than 1% of the human genome, Rho GTPases exert disproportionate control over cell division. Crucial to this master regulatory role is their localized occupation of specific domains of the cell to ensure the assembly of a contractile ring at the proper time and place. RhoA occupies the division plane and is the central positive Rho family regulator of cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 141 publications
(278 reference statements)
1
71
0
Order By: Relevance
“…The contraction of these actomyosin filaments is currently seen as the major, although not the sole, driving force that triggers furrow ingression (Wang 2005). The small GTPase RhoA controls assembly and constriction of the contractile ring by activating two parallel signaling pathways Jordan and Canman 2012). On binding the diaphanous (Dia) members of formin-homology proteins, RhoA stimulates profilin-mediated actin polymerization (Fig.…”
Section: Cleavage Furrow Ingression: Actomyosin Filaments Take Centermentioning
confidence: 99%
“…The contraction of these actomyosin filaments is currently seen as the major, although not the sole, driving force that triggers furrow ingression (Wang 2005). The small GTPase RhoA controls assembly and constriction of the contractile ring by activating two parallel signaling pathways Jordan and Canman 2012). On binding the diaphanous (Dia) members of formin-homology proteins, RhoA stimulates profilin-mediated actin polymerization (Fig.…”
Section: Cleavage Furrow Ingression: Actomyosin Filaments Take Centermentioning
confidence: 99%
“…It has been reported that RhoA/ ROCK signaling pathway regulated actin cytoskeleton and promoted actin myosin contraction, and subsequently regulated cell translocation and shrinkage (Ishizaki et al, 1996;Leung et al, 1996;Nobes and Hall, 1995;Ridley and Hall, 1992). In addition, the regulation of RhoA/ROCK signaling on actin cytoskeleton could also promote smooth muscle contraction, stress fiber formation, cell adhesion and differentiation (Chu et al, 2012;Jordan and Canman, 2012;Kishi et al, 2005;Lee et al, 2012;Maddox et al, 2012;Ruiz-Loredo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Once MgcRacGAP is phosphorylated by PLK1, ECT2 is recruited to the central spindle to activate RhoA (Burkard et al, 2009;Wolfe et al, 2009). Although this model clearly shows that MgcRacGAP is essential for RhoA activation, the functional role of the GAP domain remains elusive (Canman et al, 2008;Jordan and Canman, 2012;Loria et al, 2012). A recent study showed that MgcRacGAP inactivates Rac1 to promote furrowing in mammalian cells (Bastos et al, 2012); however, it remains unknown whether there are any mechanisms that regulate the GAP activity during cytokinesis.…”
Section: Introductionmentioning
confidence: 99%